KORELASI FENOTIP ANTARA UKURAN BAGIAN TUBUH DENGAN BOBOT BADAN DARI SILANGAN AYAM PEDAGING, KATE DAN LOKAL SABU PADA UMUR DUA BELAS MINGGU (Phenotipe correlation between body measurements with body weight of crossbreds of broiler, kate.....) - Yohanes Djego; Johny Nada Kihe (JURNAL NUKLEUS PETERNAKAN, 2020)
The aims of this research were to know the relationship between the the weight and body measurements at age of 12 weeks of crossbreds of three chicken types that were broiler, kate and sabu chicken. The relationship of body weight with the body measurements was used as a consideration for selecting the body weight. The research material was 30 tails of crossbreds with genotype composition was ½ broiler 1/4 kate ¼ sabu chicken. The method of research was experiment and directly weighting and measuring of the body measuremens. All chickens were given freely the same food and waters. The observed parameters were body weight, backbone length, chest circumference, shank circumference and wing span. Data was analized using the correlation analysis. Research results showed that the koefisien of correlation between chest circumference, backbone length, shank length and wing span with body weight were 0.62; 0.32; 031 and 0.20. Correlations between body weight and body measurements of chicken crossbreds with genotype composision ½ broiler ¼ kate ¼ sabu were positive.